P38 HEART FAILURE IN TRANSPLANTED HEART DUE TO TOXOCARA CANIS. (18th May 2022) - Zanella, L; Toscano, G; Gerosa, G
Abstract: Toxocara Canis is a parasitic roundworm which cause zoonotic infections worldwide. It could affect heart causing myocarditis, pericarditis and Loffler's endocarditis, with a clinical presentation ranged from asymptomatic to life threating conditions with heart failure. After heart transplantation, patients are immunosuppressed, therefore they could experience reactivation of hidden parasitosis like Toxocariasis. To our knowledge, some cases of Toxocara Canis affecting the heart have been described in literature, but there are no described cases of this infection in a transplanted heart. A 65–year–old woman underwent transplant heart surgery due to post–ischaemic dilatative cardiomyopathy. After transplantation she experienced supraventricular tachycardia, reduction of the new heart ejection fraction from 52% to 30% (Figure 1 ) requiring inotropic drug therapy and mild to severe mitral valve regurgitation due to ventricular dilatation. The unique finding was the presence of antibodies against Toxocara Canis in her blood and high level of immunoglobulin E. In addition, endomyocardial biopsy revealed a cystic intracellular inclusion. Specific therapy with albendazole and corticosteroids was immediately started: heart ejection fraction slowly grew up and mitral regurgitation became milder. Time correlation between Toxocara Canis antibodies positivity and worsening of heart ejection fraction, moreover the recovery with specific antibiotic therapy against this parasite, make us think that it could have been the cause of heart function deterioration in this patient. Often diagnostic findings of Toxocara Canis infection are not specific, heart damage seemed to be driven by direct invasion of the larvae and by immunological reaction. In conclusion, Toxocara Canis could be a cause of heart function deterioration after heart transplant. It should be considered in differential diagnosis of post–transplant heart failure.